Penerapan Keadilan Restoratif bagi Anak Pelaku Tindak Pidana - Hirohito, Alfonico; Saefullah, Saefullah; Mardani, Mardani (VISA: Journal of Vision and Ideas, 2024)
Nowadays, criminal acts are not only committed by adults. A child can do the same thing. For example, in the case of the Garut District Court decision Number 1/Pid.Sus-Anak/2023/PN Grt and the West Jakarta District Court Decision Number 24/Pid.Sus-Anak/2021/PN Jkt.Brt, a case regarding the crime of theft with serious aggravating circumstances. done by children. The problems discussed in this research are the legal analysis of the implementation of restorative justice for children who have committed criminal acts in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System in Decision Number 1/Pid.Sus-Anak/2023/PN Grt and Decision Number 24/ Pid.Sus-Anak/2021/PN Jkt.Brt In Result, the application of restorative justice in cases in Decision Number 1/Pid.Sus-Anak/2023/PN Grt and in Decision Number 24/Pid.Sus-Anak/2021/PN Jkt.brt, as mandated by Law Number 12 of 2012 concerning the Juvenile Justice System has reflected the realization of restorative justice for children. The application of restorative justice has been a form of legal protection for children as perpetrators during this time. The restorative justice approach exists to provide protection for children who are in conflict with the law, as well as victims of criminal acts and the community to be involved in resolving criminal cases committed by children.